2019
DOI: 10.1038/s41598-019-48369-w
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation promotes the angiogenic potential of adipose-derived stem cells

Abstract: Autologous fat transfer (AFT) is limited by post-operative volume loss due to ischemia-induced cell death in the fat graft. Previous studies have demonstrated that electrical stimulation (ES) promotes angiogenesis in a variety of tissues and cell types. In this study we investigated the effects of ES on the angiogenic potential of adipose-derived stem cells (ASC), important progenitor cells in fat grafts with proven angiogenic potential. Cultured human ASC were electrically stimulated for 72 hours after which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Table 5 summarizes a list of experiments in which various cells/nanofibrous scaffolds were applied to improve angiogenesis. As electrical stimulation can promote the angiogenesis in different tissues and cell types (including the artery [214], skeletal muscle [215], peripheral nerve [216], wound healing [217,218], endothelial cells [219,220], human mesenchymal stromal cells [221], adipose tissue-derived stem cells [222], cardiomyocytes [223], and osteoblasts [224]), it may be useful to use electrospun conducting polymer nanofibers to obtain better in vitro and in vivo results in future investigations. However, there is some evidence of using conductive polymers in hydrogel constructs with pro-angiogenic potential (such as N-carboxyethyl chitosan and oxidized hyaluronic acid-graft-aniline tetramer [225], gelatin-grafted-dopamine and polydopamine-coated carbon nanotubes [226], and polypyrrole [227]), but there is a lack of research on such polymers incorporated in electrospun nanofibers with a pro-angiogenic approach.…”
Section: Cell-laden Nanofibers For Pro-angiogenesis Strategiesmentioning
confidence: 99%
“…Table 5 summarizes a list of experiments in which various cells/nanofibrous scaffolds were applied to improve angiogenesis. As electrical stimulation can promote the angiogenesis in different tissues and cell types (including the artery [214], skeletal muscle [215], peripheral nerve [216], wound healing [217,218], endothelial cells [219,220], human mesenchymal stromal cells [221], adipose tissue-derived stem cells [222], cardiomyocytes [223], and osteoblasts [224]), it may be useful to use electrospun conducting polymer nanofibers to obtain better in vitro and in vivo results in future investigations. However, there is some evidence of using conductive polymers in hydrogel constructs with pro-angiogenic potential (such as N-carboxyethyl chitosan and oxidized hyaluronic acid-graft-aniline tetramer [225], gelatin-grafted-dopamine and polydopamine-coated carbon nanotubes [226], and polypyrrole [227]), but there is a lack of research on such polymers incorporated in electrospun nanofibers with a pro-angiogenic approach.…”
Section: Cell-laden Nanofibers For Pro-angiogenesis Strategiesmentioning
confidence: 99%
“…Regarding the DCEF treatment, it can be either constant or in different waveforms, and the frequency of the electrical current may influence the biological effects [22]. Therefore, our previous study has treated rBMSCs using DCEF in different modes, including DCEF in constant and square waves in different frequency, offset, amplitude, and duty cycle [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to chemical and biological inductions, physical cues are also applied for bone tissue engineering. Electrical stimulation (ES) has been proven to influence numerous cellular processes, including migration (via TORC2/PI3K), cell cycle, cell proliferation, and angiogenesis [20][21][22]. Therefore, different tissues, such as nerves, muscles, and cartilage, have been guided by ES to promote their development and regeneration [23].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of these scaffolds in the acquisition of normal myocardial electrical current, very few studies have been conducted on the application of electro‐conductive cell sheets in cardiac repair following ischemia 16,17 . It has been shown that electrical stimulation of certain stem cell types such as adipose‐derived stem cells can induce angiogenesis‐related proteins 18 . Besides, the exposure of neonatal rat ventricular myocytes can lead to expression of vasculature endothelial growth factor (VEGF) and it cognate receptor (VEGFR‐2) 19 …”
Section: Introductionmentioning
confidence: 99%